Modulation by luminal factors on the functions and migration of intestinal innate immunity - Higashiyama, Masaaki; Miura, Soichiro; Hokari, Ryota (Frontiers in Immunology, 2023)
Immune cell trafficking from blood stream through lymphatic organ to lymphatics is an essential function for immune responses. Luminal antigens, nutrients, metabolites from commensal bacteria, bile acids or neuropeptides influence immune cell trafficking in the intestine. The dynamics of immune cells have been investigated in gut-associated lymphoid tissues, revealing that a number of gut trophic lymphocytes repeatedly migrate from the gut to the systemic circulation via lymphatic and vascular vessels. Among the immune cells in the gut, innate lymphoid cells, including macrophages, neutrophils, dendritic cells, mast cells, and innate lymphoid cells, play an important role for the maintenance of intestinal homeostasis through a rapid immune response to luminal pathogens. However, these innate cells are influenced by several luminal factors, possibly leading to dysregulated gut immunity and intestinal disorders such as inflammatory bowel disease (IBD) and food allergy. In addition, luminal factors are sensed by distinct neuro-immune cell units, which also have a strong impact on immunoregulation of the gut. This mini-review examines knowledge of luminal and neural factors that regulate and modulate response and migration of leukocytes including innate immune cells, some of which are associated with pathological intestinal inflammation.